Insight into the role of the gut-brain axis in alcohol-related responses: Emphasis on GLP-1, amylin, and ghrelin - Tufvesson-Alm, Maximilian; Shevchouk, Olesya T.; Jerlhag, Elisabet (Frontiers in Psychiatry, 2023)
Alcohol use disorder (AUD) contributes substantially to global morbidity and mortality. Given the heterogenicity of this brain disease, available pharmacological treatments only display efficacy in sub-set of individuals. The need for additional treatment options is thus substantial and is the goal of preclinical studies unravelling neurobiological mechanisms underlying AUD. Although these neurobiological processes are complex and numerous, one system gaining recent attention is the gut-brain axis. Peptides of the gut-brain axis include anorexigenic peptide like glucagon-like peptide-1 (GLP-1) and amylin as well as the orexigenic peptide ghrelin. In animal models, agonists of the GLP-1 or amylin receptor and ghrelin receptor (GHSR) antagonists reduce alcohol drinking, relapse drinking and alcohol-seeking. Moreover, these three gut-brain peptides modulate alcohol-related responses (behavioral and neurochemical) in rodents, suggesting that the alcohol reduction may involve a suppression of alcohol’s rewarding properties. Brain areas participating in the ability of these gut-brain peptides to reduce alcohol-mediated behaviors/neurochemistry involve those important for reward. Human studies support these preclinical studies as polymorphisms of the genes encoding for GLP-1 receptor or the ghrelin pathway are associated with AUD. Moreover, a GLP-1 receptor agonist decreases alcohol drinking in overweight patients with AUD and an inverse GHSR agonist reduces alcohol craving. Although preclinical and clinical studies reveal an interaction between the gut-brain axis and AUD, additional studies should explore this in more detail.